(untitled) (Bangladesh Journal of Medicine, 2018)
Prostatic rhabdomyosarcoma is a common tumour in infancy and childhood but rare in young adults and older people. A 17-year-old boy presented with features of bladder outlet obstruction. On digital rectal examination, a growth was found in the prostate. After performing trans-rectal ultrasound guided biopsy it revealed rhabdomyosarcoma of prostate which was locally advanced, involving bladder pelvic nodes. Neoadjuvant chemotherapy with ifosfomide and doxorubicin was given for 6 cycles. However, it was still inoperable and therefore, pelvic radiotherapy was started improving the local control. Bangladesh J Medicine Jul 2018; 29(2) : 87-90